English grammar: An introduction - Peter Collins (MacMillan Press, 2000)
The book consists of two sections. The first section locates the study of grammar within its broader context, explaining the relationship between grammar and other - semantic and phonological - aspects of the study of language, and explaining the prescriptive notions that have come to be intimately associated with grammar. The second part takes a very practical approach, applying the methods learnts and developed in the first part to the analysis of a variety of texts. Exercises are provided throughout to consolidate learning, with answers provided at the end of the book.